2006
DOI: 10.1161/01.atv.0000249639.36915.04
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Leukocyte-Derived Microparticles Predict Subclinical Atherosclerosis Burden in Asymptomatic Subjects

Abstract: Objective-To clarify circulating microparticles (MP) relationships with preclinical atherosclerosis. Methods and Results-In 216 subjects without cardiovascular disease, we assessed: (1) annexin V-positive, plateletderived, endothelium-derived and leukocyte-derived circulating MP by capture on annexin V, anti-GPIb, anti-CD105, and anti-CD11a antibody-coated wells, respectively; (2) Framingham risk, metabolic syndrome, and low-grade inflammation by risk factors measurement including hsCRP; and (3) subclinical at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 35 publications
4
139
1
Order By: Relevance
“…Arteaga et al [71] reported endothelial-cell microparticle release, platelet and leukocyte activation and increased binding of microparticles from endothelial cells and platelets to leukocytes in patients with the MetS, whereas Ueba et al [72] reported that platelet microparticle levels were predictive of MetS. Chironi and colleagues [73] showed that…”
Section: Metabolic Syndrome (Mets)mentioning
confidence: 99%
See 1 more Smart Citation
“…Arteaga et al [71] reported endothelial-cell microparticle release, platelet and leukocyte activation and increased binding of microparticles from endothelial cells and platelets to leukocytes in patients with the MetS, whereas Ueba et al [72] reported that platelet microparticle levels were predictive of MetS. Chironi and colleagues [73] showed that…”
Section: Metabolic Syndrome (Mets)mentioning
confidence: 99%
“…For the moment, standardization of the method of isolation and detection of microparticles is needed [80]. [14,69] [ 72,73] …”
Section: Future Directionsmentioning
confidence: 99%
“…5 Notably, in healthy individuals, leukocyte-derived MPs were found to be associated with the component of metabolic syndrome or the Framingham risk score and were predictive of the extent of infra-clinical atheroma independently of traditional risk factors. 19 With respect to the current knowledge, we believed that the demonstration of the reduction of leukocytesderived MPs is potentially meaningful on a pathophysiological point of view. Indeed, when considering the intricate mechanisms of thrombosis, several lines of evidences pointed at a key role for leukocyte-derived MPs.…”
Section: Obesity Associated Inflammation and Vascular Damagementioning
confidence: 99%
“…17,18 For instance, in newly menopausal women, procoagulant microparticle levels increase with the decline of endogenous estrogen concentration, and thus may be indicative of the cardiovascular risk at menopause. 19 Elevation of plasma EMP levels particularly reflects cellular injury and now appears as a marker of vascular dysfunction.…”
Section: Circulating Microparticles and Vascular Dysfunctionmentioning
confidence: 99%